Internalizing Islamic School Culture to Prevent the Moral Decline of Generation Z - Nafisatus Silviya; Binti Maunah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the forms of Islamic school culture, the strategies of its internalization, and their effectiveness in addressing the moral challenges faced by Generation Z in the digital era. This research employed a qualitative approach using interviews, observations, and documentation, with data analyzed through an interactive model involving data reduction, data display, and conclusion drawing. The findings show that: (1) Islamic school culture is manifested through a Qur’anic vision, the integration of Islamic values into the curriculum, habituation of worship, teachers’ role modeling, and a consistently religious environment; (2) internalization strategies are implemented comprehensively through school leadership, value-based learning integration, Qur’anic achievement monitoring, the use of digital media, and active student participation in religious activities; (3) these strategies led to improvements in students’ discipline, responsibility, and religious awareness, as well as the creation of a conducive, bullying-free school climate and the reinforcement of Islamic practices in family environments. The findings highlight the importance of integrating digital innovation into Islamic education to enhance student engagement and ensure the relevance of value internalization in the digital era.